2018
DOI: 10.1002/lno.10786
|View full text |Cite
|
Sign up to set email alerts
|

Large but variable methane production in anoxic freshwater sediment upon addition of allochthonous and autochthonous organic matter

Abstract: An important question in the context of climate change is to understand how CH4 production is regulated in anoxic sediments of lakes and reservoirs. The type of organic carbon (OC) present in lakes is a key factor controlling CH4 production at anoxic conditions, but the studies investigating the methanogenic potential of the main OC types are fragmented. We incubated different types of allochthonous OC (alloOC; terrestrial plant leaves) and autochthonous OC (autoOC; phytoplankton and two aquatic plants species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
123
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 138 publications
(134 citation statements)
references
References 78 publications
(201 reference statements)
10
123
1
Order By: Relevance
“…The relationship between carbon source and CH 4 potential production rates was different between the solid and dissolved fraction of OM. In the dissolved portion of carbon, potential production rates were positively correlated with BIX, an indicator of OM aq , which is consistent with several reports that algal biomass is a labile carbon source readily utilized by methanogens (Schwarz et al ; Duc et al ; West et al ; Grasset et al ). The CH 4 rates were also negatively correlated with HIX and SUVA 254 , indices that represent humified and aromatic DOM.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The relationship between carbon source and CH 4 potential production rates was different between the solid and dissolved fraction of OM. In the dissolved portion of carbon, potential production rates were positively correlated with BIX, an indicator of OM aq , which is consistent with several reports that algal biomass is a labile carbon source readily utilized by methanogens (Schwarz et al ; Duc et al ; West et al ; Grasset et al ). The CH 4 rates were also negatively correlated with HIX and SUVA 254 , indices that represent humified and aromatic DOM.…”
Section: Discussionsupporting
confidence: 90%
“…This would suggest that of the total bulk pool of OM in the sediments, the aquatic‐derived portion is more readily solubilized and made available for methanogens. Both aquatic and terrestrial derived OM may be important for CH 4 production. OM aq sources may be rapidly degraded while terrestrial OM is degraded over both short and longer time scales (see Guillemette et al ; Grasset et al ). Overall, the riverine zone receives more OM than the other zones, including substantially greater amounts of terrestrial OM.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the significant potential of trapping OC in the sediment, reservoirs can be strong sources of methane (CH 4 ) to the atmosphere (Deemer et al, 2016). Several studies have shown a positive relationship between CH 4 production and temperature in freshwater ecosystems (Marotta et al, 2014;Wik et al, 2014;Yvon-Durocher et al, 2014;Aben et al, 2017), and also organic matter supply to sediment is an important regulator of CH 4 production and emission (Segers, 1998;Sobek et al, 2012;Grasset et al, 2018). Thus, tropical reservoirs, especially those situated in highly productive humid tropical biomes, such as the Amazon, may produce more CH 4 than temperate ones due to higher annual temperatures and availability of organic matter in their sediments (Barros et al, 2011;Mendonça et al, 2012;Fearnside and Pueyo, 2012;Almeida et al, 2013), although highly emitting reservoirs can also be situated in temperate regions (Deemer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Lakes are releasing CH 4 to the atmosphere at globally important rates, even though they cover a relatively small area (Bastviken et al 2011;Kirschke et al 2013). Although CH 4 can be directly produced in the surface water of lakes (Bogard et al 2014;Donis et al 2017), the majority derives from the anoxic sediments as a result of anaerobic degradation of deposited organic carbon (Bastviken et al 2004b;Grasset et al 2018). To reach the atmosphere, sedimentproduced CH 4 must be transported through the water column, where it can be consumed by methanotrophs (Rudd and Hamilton 1978;Utsumi et al 1998;Kankaala et al 2006;Bastviken et al 2008).…”
mentioning
confidence: 99%